Hypoglycemic and Hypolipidemic Activities of Bile of Bangladeshi Labeo rohita on Streptozotocin (STZ) - Induced Diabetic Rats (Bangladesh Pharmaceutical Journal, 2022)
Diabetes mellitus (DM) is one of the most commonly diagnosed condition all over the world. Fish is a typical delicacy and one of the most nutritious foods available. Fresh fish bile, according to various indigenous healthcare professionals in Bangladesh, has anti-diabetic effects and its importance in the treatment or management of diabetes and cardiovascular illnesses has also been documented in few recent studies. The goal of this work was to test the hypoglycemic potential of Labeo rohita bile content in order to objectively validate this folklore claim. In this study, in-vivo investigation of the hypoglycemic and hypolipidemic activities of L. rohita bile was performed against a streptozotocininduced diabetic rat model. Rats were given bile extract at doses of 0.08 ml/kg body weight and 0.16 ml/kg body weight for one week. Here, metformin HCl (100 mg/kg body weight) was used as reference standard. Both the doses of bile extract exhibited significant hypoglycemic effect (p